IDENTIFIKASI TEMPAT PERINDUKAN BUATAN LARVA Aedes aegypti DAN PELAKSANAAN 3M PLUS DI KELURAHAN BANGKA BELITUNG DARAT KECAMATAN PONTIANAK TENGARA KOTA PONTIANAK - ., Riyang Pradewa Admawan (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Dengue Hemorrhagic Fever (DHF) is an infectiondisease that caused by dengue virus through bites of Aedes aegypti.Pontianak city is one of DHF endemic areas and Bangka Belitung Daratvillage is an area that has the highest incidence rate in Pontianak city.Objectives: The aims of this research are to know the density figure oflarvae of the Aedes aegypti mosquito, the actions of 3M plus and to knowthe classification of the water container that dominant of larvae of theAedes aegypti mosquito. Methods: This research was designed as across-sectional descriptive survey. This research conducted in March2014. The amount of sample were 100 respondents that collected withentomology survey and using the questionnaire instrument. Purposivesampling used for the sampling technique and the data was analyzed byusing descriptive statistic method. Results: The result of the researchshowed that 64% respondents do draining the bathing container, 90%covering the water container, 83% removing unused things, 34% usingmosquito net, 92% using repellent, 75% using temephos, 10% raise awiggler eating fish, 69% installing wire netting, 87% hanging shirt in thebedroom, and 7% replacing the water of flower vase and drinking place ofthe bird. Index of larvae of the Aedes aegypti mousquito were 13,7% ofcontainer index (CI), 42% of house index (HI), and 96 of breteau index(BI). Conclusions: The density figure of larva of the Aedes aegypti basedon CI was 4, BI was 7, HI was 6 and the water container that dominant oflarva of the Aedes aegypti is cement crock.Keywords: Dengue Hemorraghic Fever, Larvae Index, Implementations of3M Plus1. Department of Parasitology, Medical Faculty, Tanjungpura University,Pontianak, West Borneo2. Department of Public Health, Medical Faculty, Tanjungpura University,Pontianak, West Borneo3. Medical Faculty, Tanjungpura University, Pontianak, West Borneo